The Maqasid Syari'ah Paradigm as an Offering for Family Resilience: An Analysis of Maqasid Syari'ah Thought by Alal Fasi - Muafi, Muafi; Arfan, Abbas; Wahid, Ziadul Ulum (Al-Syakhsiyyah: Journal of Law and Family Studies, 2025)
Family resilience is a crucial issue these days. Data shows that hundreds of thousands of couples in Indonesia fail to maintain their marriages and end up divorcing. This paper aims to provide solutions to these cases by offering a new paradigm for maintaining families, namely by proposing the Maqasid Syari’ah (objectives of Islamic law) as conceived by Alal al-Fasi. This research is a type of library research with a descriptive and interpretative analytical approach. There are two types of data in this research: primary data obtained from books written by Alal Fasi and secondary data in the form of books, journals, and other written sources of information. The results of this study show that Alal al-Fasi's Maqasid Syari’ah thinking is very relevant to be applied and used as a paradigm to achieve family resilience. This proposal is formulated into two parts. First, to create family resilience, it is necessary to integrate psychological, moral, and spiritual aspects, which are realized through the fulfillment of human rights in the household, such as the needs for clothing, food, and shelter. Second, by understanding maqasid as a husband and carrying out the two great mandates given by the Qur'an, namely as qawam, the leader of the household, which emphasizes obligations from a material and moral aspect, and the obligation to protect the family from the fires of hell, which emphasizes the spiritual aspect.